Proses Berpikir Analitis Siswa SMA dalam Menyelesaikan Soal Pemecahan Masalah Matematika Ditinjau dari Kemampuan Matematika - Hasnia Firdaus; Ismail Ismail (Program Studi S1 Matematika UNESA, 2023)
Analytical thinking is a person mental activity in problem solving by separating in important parts of a problem, looking for relationships between these parts, the drawing conclusions from problem solving. The analytical thinking skills possessed by student will have an impact on their ability to solve a problem. In solving mathematical problems, apart from paying attention to analytical thinking skills, it also pay attention to students mathematical abilities. The purpose of this research is describe the analytical thinking processes of senior high school students with high, medium, and low mathematical abilities in mathematical problem solving. The research approach used is a descriptive qualitative. The research subject consisted of three students from class X-4 SMA Hangtuah 2 Sidoarjo. The research data were obtained from the result of math ability test, math problem solving test, and interviews. The results showed that (1) Students with high mathematical abilities completed 2 problem solving questions properly and correctly. Students distinguish an important part of a given problem. Students plan strategies that will be used to solve problems, and carry out these strategies appropriately. Students re-examine the completion process that has been carried out. (2) Students with mathematical abilities are completing 2 problem solving questions correctly. Students distinguish an important part of a given problem. Students plan the steps that will be used to solve the problem, as well as carry out the strategies that have been made before. Students do not re-check the completion process carried out. (3) Students with low mathematical ability solve 1 problem out of 2 problem solving questions given. Students distinguish important parts of a given problem. Students plan strategies that will be used to solve problems. However, in carrying out the settlement plan that has been made, students experience difficulties. Therefore, students do not get a solution to the problem given. Students do not re-examine the completion that is done.